Are the apocarotenoids content and colorimetric traits of saffron (Crocus sativus L.) affected by some post harvesting operations?. (May 2022) - Aghhavani Shajari, Mahsa; Rezvani Moghaddam, Parviz
Abstract: Saffron quality is strongly affected by post-harvest practices. In this regard, an experiment was conducted to evaluate the effect of flowers storage temperature (2, 8, and 21 °C) and storage duration (1, 2, 3, and 4 days) on color traits ( L, a, b, o h, and C ), apocarotenoids content (crocin, picrocrocin, and safranal, determined by HPLC and spectrophotometry methods), antioxidant compounds (anthocyanin and total phenol) and microbial load of dried stigmas and petals. The color quality of the stigma ( L, a, C, and o h ) improved by one day storing at two °C. HPLC analysis revealed that the highest contents of crocin, picrocrocin, and safranal in stigma were gained by one day storing at 2 °C, although the stigma quality was even acceptable in longer storing when storage temperature was low. A positive correlation between crocin and picrocrocin contents with color parameters ( L, a, and C ) suggests that colorimetry can be possibly used as a fast, easy, and cheap method for stigma quality assessment. The highest amounts of anthocyanin in stigma and petal (4167 and 9663 g 100 g −1 dry weight, respectively) were obtained at two °C and three days storing. Petal had more anthocyanin content than stigma in all storage duration and temperature combinations. The total count of microorganisms in stigma and petals decreased by reducing storage duration and temperature. Overall, lower storage temperature and shorter storage duration were more favorable for improving stigma and petals quality, but low storage temperature can compensate for the negative effect of longer storage duration. Highlights: The highest main compounds of saffron stigma were identified in one-day storage at 2 °C using HPLC. There is a positive correlation between crocin and picrocrocin contents with color traits. Colorimetry could be used as a fast, easy, and cheap method for saffron stigma quality assessment. Low storage temperature can compensate for the negative effect of more extended storage days. Petal as a by-product had more anthocyanin content than stigma in all storage duration and temperatures treatments.